Technology Acceptance Model (TAM) on Banking: A Review - Mimma Maripatul Uula; Sherrindra Avedta (Islamic Marketing Review, 2023)
This study aims to see the development of Technology Acceptance Model (TAM) on Banking research around the world and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "TAM on Banking" which comes from the Scopus database with a total of 583 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "TAM on Banking" research development in the world. The results of the study found that on bibliometric author mapping the authors who published the most research on the theme "TAM on Banking" were Chawla D.; Joshi H; Belousova V.; Chichkanov N; Baptista G.; Oliveira T.; Maduku D. K; Changchit C.; Lonkani R.; Samp; and Saxena N.; Gera N.; Taneja M.. Furthermore, based on bibliometric keyword mapping, there are 5 clusters that can become research paths with topics related to (1)Technology Adoption in Banking and its Influential Factors, (2)Acceptance of Technology in Banking, (3)Technological Innovation in the Banking Sector, (4)Mobile Banking Service Adoption, and (5)Risks in Online Banking Services.